PENGARUH TEKNIK POLIMERISASI EMULSI TERHADAP UKURAN PARTIKEL KOPOLI(STIRENA/BUTIL AKRILAT/METIL METAKRILAT) - Budianto, Emil; Nizardo, Noverra Mardhatillah; Utari, Tresye (UI Scholars Hub, 2018)
Influence of Emulsion Polymerization Techniques to Particle Size of Copoly(styrene/butyl acrylate/methyl methacrylate). In the majority of applications, particle size and particle size distribution are highly significant factors that determine the properties of a polymer dispersion, such as its flow behavior or its stability. For example, a coating material with small particle size will give smooth coating result, good adhesive strength, good water resistance and latex stability. This article describes influence of various emulsion polymerization techniques to particle size of copoly(styrene/butyl acrylate/methyl methacrylate) with mix surfactant SDBS linear chain and nonyl fenol (EO10) and initiator ammonium persulphate. DSC data, solid content and IR spectrum showed that copoly(styrene/butyl acrylate/methyl methacrylate) was produced. Batch emulsion polymerization technique gave the highest particle size i.e. 615 nm and also the highest % conversion of monomer i.e. 97%. The more concentration of monomer was seeded to initial charge gave greater particle size and greater poly dispersity index.